In-vitro accuracy of complete arch scans of the fully dentate and the partially edentulous maxilla - Waldecker, Moritz; Bömicke, Wolfgang; Behnisch, Rouven; Rammelsberg, Peter; Rues, Stefan (Journal of prosthodontic research, 2022)
Purpose: This in-vitro study aimed to compare the accuracy of complete arch scans (CAS) of a fully dentate (FD) and a partially edentulous (PE) maxillary model. Three intraoral scanning systems were used: Omnicam AC (OC), TRIOS 4 (TR), and Primescan (PS). - Methods: Each intraoral scanner was used to take 30 scans each of two clinical scenarios (FD and PE) simulated by a reference model. The PE model simulated a maxilla with six prepared teeth to accommodate a jaw-spanning fixed partial denture (FPD). The missing teeth were then added to create an FD model. Five ceramic precision balls (ball centers P1-P5) mounted on metal pins were welded to the metal base on the buccal side of the dental arch. These were later used to determine dimensional (given by each 2 ball centers) and angular changes (given by each 3 or 4 ball centers) between the reference model (digitized with high precision before the tests) and the intraoral scans. Data were statistically analyzed using a type II ANOVA. - Results: The maximum mean absolute distance deviations were as follows. OC: 147 µm (FD) and 139 µm (PE). TR: 133 µm (FD) and 136 µm (PE). PS: 87 µm (FD) and 80 µm (PE). The scanning system used had a significant effect on distance deviations (p < 0.027) and CAS scanning time (p < 0.001). Dental status had no clear effect on distance deviations but did significantly affect angular changes (p < 0.001) and scanning time (p < 0.001). - Conclusion: The manufacture of jaw-spanning FPDs based on a CAS cannot yet be recommended.